Simulation of synchronous machine model and analysis of fault and load transient - Heng, Wei Shyong (2017)
The basis of the project is to design and analyze a system consisting of a synchronous generator that supplies a three phase active load through a three-phase diode rectifier with AC excitation as the primary mean of excitation. The model is subjected to different fault and load situations for the study of transient dynamics. The design and simulation was carried out in MATLAB environment. The objective of the dissertation is to achieve a model which, under a simulated environment of a synchronous generator system’s control-loops under different fault and load situation. The results were studied to understand the simulated load and fault dynamics of the system and produce a data based analysis of the system and its components.